The Mediating Role of Accounting Information Systems in Determining MSME Performance - Ni Wayan Sri Tresna Egawati; I Gusti Ayu Purnamawati; Edy Sujana (Jurnal Ilmiah Akuntansi, 2023)
This study explores the impact of institutions, human resources, finance, and marketing on accounting information systems and their consequential effects on MSME performance in Jembrana Regency. Focused on 126 MSMEs in the culinary sector, initially struggling, the research is crucial for the region's economic progress. Utilizing convenience sampling, the study employs SEM-PLS with SmartPLS Version 3 software for data analysis, considering unobserved variables. Findings reveal a significant positive influence of institutions, human resources, finance, and marketing on the MSME accounting information system. Moreover, the accounting information system acts as a mediator, translating these influences into positive outcomes for MSME performance. These insights not only guide the Jembrana Regency Government in formulating policies to enhance the accounting information system and MSME performance but also offer valuable considerations for MSME players aiming to refine competitive strategies. This research contributes to financial accounting, accounting information systems, and strategic management fields, providing a nuanced understanding of the interconnected dynamics. As the first comprehensive study of its kind in the Jembrana Regency, these findings serve as a foundational reference for future research in related domains.